PERAN PENGETAHUAN, DUKUNGAN KELUARGA, DAN EFEK SAMPING TERHADAP KEPATUHAN SUPLEMENTASI ZAT BESI PADA IBU HAMIL - Maharani Siswanti; Salsabila (Jurnal Kesehatan Sejahtera, 2025)
Iron deficiency anemia remains a major public health problem and contributes significantly to maternal morbidity and adverse birth outcomes. In Indonesia, the prevalence of anemia among pregnant women reached 48.9% in 2018 despite high coverage of iron tablet distribution. Low medication adherence remains a key barrier to program effectiveness. This study aimed to analyze factors associated with adherence to iron supplementation among pregnant women at the Midwifery Clinic of RSUD Maluku. An analytic observational study with a cross-sectional design was conducted among 60 pregnant women in their second and third trimesters. Data were collected using structured questionnaires and pill count methods, and analyzed using Chi-Square test. The results showed significant associations between adherence and knowledge (p = 0.002), family support (p = 0.001), and perceived side effects (p = 0.014). Pregnant women with good knowledge and strong family support were more likely to adhere to iron supplementation, while discomfort from side effects acted as a barrier. Strengthening health education and involving family members as treatment supervisors are recommended to improve adherence and reduce anemia prevalence